1989
DOI: 10.1152/jappl.1989.67.5.1820
|View full text |Cite
|
Sign up to set email alerts
|

Work capacity during 30 days of bed rest with isotonic and isokinetic exercise training

Abstract: The purpose was to test the hypothesis that twice daily, short-term, variable intensity isotonic and intermittent high-intensity isokinetic leg exercise would maintain peak O2 uptake (VO2) and muscular strength and endurance, respectively, at or near ambulatory control levels during 30 days of -6 degrees head-down bed rest (BR) deconditioning. Nineteen men (aged 32-42 yr) were divided into no exercise control (peak VO2 once/wk, n = 5), isokinetic (Lido ergometer, n = 7), and isotonic (Quinton ergometer, n = 7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
87
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 0 publications
7
87
0
Order By: Relevance
“…76,77 Following an 11-day human spaceflight, Edgerton et al 78 observed a significant decline in Short-term space flight (17 days) was found to reduce specific tension of soleus muscle fibers. 80 Although human data from Skylab and Mir suggest that leg extensors atrophy and loose peak force faster than flexors, when flight duration is long enough (4200 days) both groups of muscles show similar declines of B30 % in isokinetic strength. 73,79 Interestingly, in both patients with SCI and astronauts following spaceflight, there seem to be alterations in the contractile apparatus (Figure 3), which could also contribute to the impairment in muscle force.…”
Section: Muscle Atrophymentioning
confidence: 99%
“…76,77 Following an 11-day human spaceflight, Edgerton et al 78 observed a significant decline in Short-term space flight (17 days) was found to reduce specific tension of soleus muscle fibers. 80 Although human data from Skylab and Mir suggest that leg extensors atrophy and loose peak force faster than flexors, when flight duration is long enough (4200 days) both groups of muscles show similar declines of B30 % in isokinetic strength. 73,79 Interestingly, in both patients with SCI and astronauts following spaceflight, there seem to be alterations in the contractile apparatus (Figure 3), which could also contribute to the impairment in muscle force.…”
Section: Muscle Atrophymentioning
confidence: 99%
“…Also of interest is that the cycling countermeasure of Greenleaf et al 1989 prevented a decrease in plasma volume while a similar exercise regime of Shibata et al 2010 did not prevent the decrease. The treatment group in the Greenleaf study had two bouts of 30 minutes of cycling for five days per week at an intensity that varied from 40% to 90% of their pre-bed rest VO 2 max.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The AG group was not significantly Note that the outlier in the AG countermeasure group was the Katayama et al 2004 study, which coupled AG with intensive cycling. In addition, the upper whisker of the traditional countermeasures group was from the Greenleaf et al 1989 study, which used only intensive cycling as the countermeasure.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…It is kept implicit that these statements apply to _ V O 2max measurements in upright posture shortly after the end of the bed rest period. In fact, this is not so during bed rest (or space flight), or in supine posture after bed rest, since very small changes, if any, in _ V O 2max were found in these conditions (Bringard et al 2010;Greenleaf et al 1989;Levine et al 1996;Trappe et al 2006).…”
Section: Of Maximal Oxygen Consumption At the End Of Bed Restmentioning
confidence: 92%
“…Moreover, in this experimental model, only the duration of the bed rest period varies among studies, allowing a precise evaluation of the time courses of the functional modifications induced by bed rest. _ V O 2max decreases after bed rest (Bringard et al 2010;Capelli et al 2006;Convertino et al 1982;Ferretti et al 1997a;Greenleaf et al 1989;Kashihara et al 1994;Saltin et al 1968;Stremel et al 1976;Trappe et al 2006), even of very short duration (Smorawinski et al 2001). The size of the _ V O 2max decrease is larger the longer is the bed rest duration, being fast in the first days, and progressively slower as bed rest proceeds.…”
Section: Of Maximal Oxygen Consumption At the End Of Bed Restmentioning
confidence: 98%